Sequential development of peripheral t-cell lymphoma post immunochemotherapy of diffuse large B cell lymphoma. Issue 4 (3rd April 2017) - Wang, Jing-Wen; Chen, Jia-Yan; Lu, Chen; Tang, Xi
ABSTRACT: Reports of sequential occurrence of two or more types of lymphoma are rare, especially when they involve different cell lineages. Herein, we report a rare case of sequential development of peripheral t-cell lymphoma following treatment of diffuse large B cell lymphoma. In a 73-year-old Chinese male patient, diffuse large B-cell lymphoma (DLBCL) was diagnosed in September 2011 based on the result of a tongue biopsy. Afterwards, he received rituximab combined with chemotherapy and local radiotherapy. Though he achieved completed remission, he had a new symptom of one enlarged left inguinal lymph node in November of 2015. A new biopsy was then performed. Immunohistochemistry and polymerase chain reaction (PCR) for gene rearrangements proved monoclonal T-cell lymphoma. We didn't detect EBV infection in either of two biopsies, nor any evidence of immune dysfunction complications. Sequential development of B-cell and T-cell malignancy in this patient maybe an example of treatment-related secondary lymphoma.